2011
DOI: 10.1021/ac201223d
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating N-Terminal Aspartic and Isoaspartic Acid Residues in Peptides

Abstract: Formation of isoaspartic acid (isoAsp) is a common modification of aspartic acid (Asp) or asparagine (Asn) residue in proteins. Differentiation of isoAsp and Asp residues is a challenging task owing to their similar properties and identical molecular mass. It was recently shown that they can be differentiated using ion-electron or ion-ion interaction fragmentation methods (ExD), as these methods provide diagnostic fragments c + 57 and z• − 57 specific to the isoAsp residue. To date, however, the presence of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 51 publications
1
25
0
Order By: Relevance
“… 13 Previous reports characterizing stereoisomers of synthetic Aβ have particularly demonstrated that isomerization at position Asp-1 and Asp-7 is frequent. 23 , 38 , 52 However, neither the extent of isomerization of Asp-1 and Asp-7 residues in Aβ 1 – 15, Aβ 2 – 15 , Aβ 3Glu-15 and Aβ 4 – 15 have been directly measured in human brain nor has a systematic study been conducted using ion mobility to determine the effect of isomerization on the structure of these peptides in the gas phase. We postulated that the orthogonality of the online LC and drift tube ion mobility separations (DT-IMS) would provide the required analytical resolution, even if at modest R ∼ 50, to resolve the N-terminal Aβ isomers/racemers derived from Alzheimer’s disease brains and improve the detection/quantification limits of these complex biological samples.…”
Section: Resultsmentioning
confidence: 99%
“… 13 Previous reports characterizing stereoisomers of synthetic Aβ have particularly demonstrated that isomerization at position Asp-1 and Asp-7 is frequent. 23 , 38 , 52 However, neither the extent of isomerization of Asp-1 and Asp-7 residues in Aβ 1 – 15, Aβ 2 – 15 , Aβ 3Glu-15 and Aβ 4 – 15 have been directly measured in human brain nor has a systematic study been conducted using ion mobility to determine the effect of isomerization on the structure of these peptides in the gas phase. We postulated that the orthogonality of the online LC and drift tube ion mobility separations (DT-IMS) would provide the required analytical resolution, even if at modest R ∼ 50, to resolve the N-terminal Aβ isomers/racemers derived from Alzheimer’s disease brains and improve the detection/quantification limits of these complex biological samples.…”
Section: Resultsmentioning
confidence: 99%
“…ETD utilized an electron transfer in gas-phase ion-ion chemistry, causing rearrangement with cleavages of the N-C α backbone referred to as c and z ions [60]. While the fragment ratios seen in CID differ suggesting structural discontinuity between the peptides, ETD cleaves the isomers of Asp producing "reporter" ions in isoAsp not seen in Asp [61]. These reporter ions are a result of an alternate cleavage due to presence of the extra methylene group in the peptide backbone of isoAsp (Figure 7).…”
Section: Confirmatory De Novo Sequencing Of Pcatx-1a and Pcatx-1b By Etdmentioning
confidence: 99%
“…Two major isozymes of PIMT have been isolated from human erythrocytes via isoelectric focusing (Ota et al, ). Although PIMT minimizes accumulation of potentially detrimental isoAsp in aged proteins, the repair process is unable to restore Asn residues, hence the effects of deamidation are partly irreversible (Yang & Zubarev, ; Sargaeva et al, ). PIMT expression appears to differ between tissues, and in rat brain the enzyme is slowly upregulated after birth and remains highly expressed throughout natural aging (Mizobuchi et al, ).…”
Section: Recent Technological Advances In the Study Of Protein Deamidmentioning
confidence: 99%